Flexible work organization and employer provided training: Evidence from German linked employer-employee data - Annika Campaner; John S. Heywood; Uwe Jirjahn (Kyklos, 2022)
We examine the hypothesis that flexible work organization involves greater skill requirements and, hence, an increased likelihood of receiving employer provided training. The analysis is based on unique linked employer-employee data from Germany for the years 2012, 2014 and 2016 (12,924 pooled observations from 9,440 employees in 1,903 establishments). Our results confirm that employees are more likely to receive training when their jobs are characterized by greater decision-making autonomy and task variety, two essential elements of flexibility. Critically, the training associated with workplace flexibility does not simply reflect technology. Skill-biased organizational change plays its own role. Moreover, we show that the training associated with workplace flexibility is disproportionately oriented toward employees with a greater formal education. We find little evidence of an age or a gender bias of workplace flexibility.
Keywords: 300